The use of zeolite, active carbon, and clove oil in closed transportation of giant freshwater prawn juvenile - Rahma Vida Anandasari; Eddy Supriyono; Odang Carman; Kukuh Adiyana (Jurnal Akuakultur Indonesia)
ABSTRACT